2008
DOI: 10.1111/j.1365-2818.2008.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved fluorescence lifetime mapping of enzyme kinetics in living cells

Abstract: SummaryTraditional cuvette-based enzyme studies lack spatial information and do not allow real-time monitoring of the effects of modulating enzyme functions in vivo. In order to probe the realistic timescales of steric modifications in enzymesubstrate complexes and functional binding-unbinding kinetics in living cells without losing spatial information, it is imperative to develop sensitive imaging strategies that can report enzyme kinetics in real time over a wide dynamic range of timescales. Here we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…Our laboratory and other groups have shown that these altered metabolic profile (“metabolic switch” or “aerobic glycolysis”) in cancer cells can be exploited for early detection. [9, 11, 18, 25, 26, 29] In order to test if the normal and cancer cells display differential mitochondrial response to glucose stimulus, we monitored steady state kinetics of mitochondrial membrane potential in MCF10A and MCF7 cells (Figure 2a & 2b). Despite the near-equal mean TMRM fluorescence in both these cell lines (Figures 1d & 1e), glucose stimulus elicited significantly different TMRM response in these two cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory and other groups have shown that these altered metabolic profile (“metabolic switch” or “aerobic glycolysis”) in cancer cells can be exploited for early detection. [9, 11, 18, 25, 26, 29] In order to test if the normal and cancer cells display differential mitochondrial response to glucose stimulus, we monitored steady state kinetics of mitochondrial membrane potential in MCF10A and MCF7 cells (Figure 2a & 2b). Despite the near-equal mean TMRM fluorescence in both these cell lines (Figures 1d & 1e), glucose stimulus elicited significantly different TMRM response in these two cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we need to adopt a pragmatic approach of combining more than one technique in the same screening setting to maximize the information content from the metabolic imaging sessions. Optical imaging provides high molecular specificity whereas tomography and magnetic resonance methods provide better depth information than the optical imaging techniques [6,[30][31][32][33][34][35]. However, by a strategic combination of these two different techniques can yield a synergistic edge to metabolic imaging of tumor-specific signatures.…”
Section: Preclinical Technologies For Probing Tumor Metabolismmentioning
confidence: 99%
“…Because excitation in the 350-450-nm wavelength range is highly toxic to cells, and because shifts in the emission spectra due to molecular interactions in cells make the analysis difficult, this approach of metabolic mapping in living cells and tissues became obsolete. However, the application of dual-photon excitation of NADH at 730 nm, which reduces cytotoxicity considerably, the determination of the ratio of free and protein (enzyme)-bound NADH using fluorescence lifetime imaging microscopy and anisotropy of autofluorescence, and the application of fast photon detection re-introduced NADH as an attractive probe for spatially resolved imaging of the metabolism of living cells (Ramanujam et al 1994;Bird et al 2005;Ramanujan et al 2008;Yu and Heikal 2009). The focus of these studies is particularly on metabolic mapping of normal and malignant cells and tissues.…”
Section: Endogenous Fluorescent Metabolitesmentioning
confidence: 99%
“…Therefore, localization or measurement of mRNA or protein of an enzyme in cells cannot predict its activity in those cells (Figure 1) (Hazen et al 2000;Baruch et al 2004;Boonacker et al 2004;Bogyo and Cravatt 2007). Similarly, activity measurements of a purified enzyme in either diluted solutions or in tissue or cell homogenates probably do not reflect the activity of that enzyme in the crowded com-partmentalized cell Ramanujan et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation